1983
DOI: 10.1017/s0022172400059994
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella isolation from reptilian faeces: A discussion of appropriate cultural techniques

Abstract: SUMMARYA short study of salmonella isolation from reptile faeces is described. The samples came from the reptile house at the Bristol Zoological Gardens. The wide range of salmonella serotypes present in the material, including representatives of all four subgenera, is noted. The important factors in the technique of isolation are discussed. These are choice of inoculum, enrichment medium, and plating medium, use of multiple subculture and serological isolation. If the number of samples available is scanty, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…For example: animal number 06 (4 Citrobacter), number 11 (2 Kluyvera), number 12 (2 Proteus) and number 07 (3 Salmonella). In fact, in a single reptile, more than 1 serotype of Salmonella can be found (Jephcott et al, 1969;Harvey and Price, 1983;Onderka and Finlayson, 1985;Van Der Walt et al, 1997;Madsen et al, 1998;Johnson-Delaney, 2006).…”
Section: Enterobacteriaceae Enterobacteriaceae Enterobacteriaceae Entmentioning
confidence: 99%
See 1 more Smart Citation
“…For example: animal number 06 (4 Citrobacter), number 11 (2 Kluyvera), number 12 (2 Proteus) and number 07 (3 Salmonella). In fact, in a single reptile, more than 1 serotype of Salmonella can be found (Jephcott et al, 1969;Harvey and Price, 1983;Onderka and Finlayson, 1985;Van Der Walt et al, 1997;Madsen et al, 1998;Johnson-Delaney, 2006).…”
Section: Enterobacteriaceae Enterobacteriaceae Enterobacteriaceae Entmentioning
confidence: 99%
“…Different authors report that the microorganisms normally found as microbiota components of the digestive system can act as etiological agents of gastrointestinal diseases in reptiles, but there are few researchers who have defined them for the Brazilian species of reptiles. The reports are scarce and many of them are outdated (Moreno et al, 1973;Belluomini et al, 1977;Iizuka et al, 1984;Calixto et al, 1986;Sá and Solari, 2001).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…The use of tetrathionate and Rappaport-Vassiliadis broths in conjunction with BSA was used for Salmonella isolation as recommended by Harvey and Price (1983) where a variety of media is required to cope with the different serotypes. Routinely, Brilliant Green Agar is used in our laboratory for Salmonella isolation as well.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella serovars, especially Salmonella subsp 111, are frequently isolated from healthy reptiles, including crocodiles and are part of the normal flora of the intestine of these reptiles (Chicdini and Sundberg 1981;Harvey and Price 1983;Debyser and Zwart 1991;Obwolo and Zwart 1993). These serotypes have rarely been incriminated as the cause of gastro-enteritis in man (Chiodini and Sundberg 1981 ;Ladds and Donovan 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of suspect colonies was performed by traditional biochemical reactions, including appropriate reactions on XLT4, BGN, MacConkey agar plates, and triple sugar iron-lysine iron agar. 3,6 One colony from each plate is selected to either inoculate the water blank directly or to enhance the growth and ensure purity for identification, a trypticase soy broth is used. Identification is performed using gram-negative identification plate, which is also known as Sensititre's Automated Microbiology System's AP80 panel (Sensititre Microbiology System Division, AccuMed International, Inc., Westlake, Ohio 44145, USA).…”
Section: Methodsmentioning
confidence: 99%